1992
DOI: 10.1126/science.1373908
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Plasma Membrane Recycling by CFTR

Abstract: The gene that encodes the cystic fibrosis transmembrane conductance regulator (CFTR) is defective in patients with cystic fibrosis. Although the protein product of the CFTR gene has been proposed to function as a chloride ion channel, certain aspects of its function remain unclear. The role of CFTR in the adenosine 3',5'-monophosphate (cAMP)-dependent regulation of plasma membrane recycling was examined. Adenosine 3',5'-monophosphate is known to regulate endocytosis and exocytosis in chloride-secreting epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
154
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(164 citation statements)
references
References 20 publications
9
154
0
1
Order By: Relevance
“…It is thus possible that both CFTR and F508del-CFTR lie mostly in the subapical region and that, upon stimulation (eg, by cAMP) CFTR, but not F508del-CFTR, undergoes exocytosis to the apical membrane, as first suggested by Bradbury et al (1992) and also by other authors (Biwersi et al, 1996;Prince et al, 1994;Takahashi et al, 1996;Tousson et al, 1996). The fact that a number of other studies reported apparently contradictory observations (Dho et al, 1993;Dunn et al, 1994;Hug et al, 1997), provides evidence that the issue of CFTR and vesicular trafficking is still an open Double labeling of CFTR, calnexin, p58, and tubulin.…”
Section: Penque Et Almentioning
confidence: 79%
“…It is thus possible that both CFTR and F508del-CFTR lie mostly in the subapical region and that, upon stimulation (eg, by cAMP) CFTR, but not F508del-CFTR, undergoes exocytosis to the apical membrane, as first suggested by Bradbury et al (1992) and also by other authors (Biwersi et al, 1996;Prince et al, 1994;Takahashi et al, 1996;Tousson et al, 1996). The fact that a number of other studies reported apparently contradictory observations (Dho et al, 1993;Dunn et al, 1994;Hug et al, 1997), provides evidence that the issue of CFTR and vesicular trafficking is still an open Double labeling of CFTR, calnexin, p58, and tubulin.…”
Section: Penque Et Almentioning
confidence: 79%
“…Forskolin, which raised intracellular cAMP, stimulated C1-secretion by increasing the magnitude of CFTR-mediated C1 conductance in the apical membrane [32], by a PKAdependent stimulus, was capable of stimulating mucin secretion in a Ca2+-independent manner [33]. In addition, the above mentioned results of McPherson and Dormer [29] who have shown a defect in [3-adrenergic stimulation of mucin and serous protein secretion from submandibular salivary tissues from CF patients and those of Bradbury et al [34] demonstrating the correction by transfection of wild type CFTR, of the defect in cAMP-mediated endocytosis and exocytosis in CFPAC-1 cells also correlated closely with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…[49]), very little is known about the dynamic participation of CFTR in this process. Immunolocalization assessment, reflecting the steady-state distribution of CFTR, is hampered both by the lack of highly specific anti-CFTR antibody and the low copy-number of CFTR.…”
Section: Discussionmentioning
confidence: 99%